Ayu Imaria Wahyuliarmy PENGARUH COGNITIVE-BEHAVIOR GROUP THERAPY TERHADAP PENURUNAN TINGKAT KECEMASAN BERBICARA DI DEPAN UMUM PADA MAHASISWI PATTANI-THAILAND DITINJAU DARI LAMA STUDI DI IAIN TULUNGAGUNG - Wahyuliarmy, Ayu Imasria (Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Women Students of Pattani-Thailand who study in IAIN Tulungagung is going through the phase moving from one place to another. Obstruction in communication or speaking makes women students of Pattani-Thailand experiencing anxiety of speaking to the public.The objective of the Study is to know the influence of cognitive-behavior group theory towards a decrease degree of speaking anxiety to the public of Pattani-Thailand women students in IAIN Tulungagung and the difference of a decrease degree of speaking anxiety to the public between students who have been studying about two years and one year in IAIN Tulungagung. The number of the sample is eight students who are divided into two categories: four women students who have been studying in IAIN Tulungagung about two years, and four women women students who have been studying about one year.The Result of statistical analisis using wilcoxon test shows that the program of cognitive-behavioral group theory is effective to decrease anxiety of speaking to the public of Pattani-Thailand women students. Mann-Whitney statistical test shows that decrease anxiety of speaking to the public in women students who have been studying in IAIN Tulungagung. Key words: Cognitive-behavior group theory, Speaking anxiety to the public, Pattani-Thailand women student.